O papel da escola com a formação inicial do professor no momento de estágio: limites, desafios e perspectivas - Custodio, Cândida Maria de Sousa (2010)
This research aimed at knowing, by means of Curricular Pre-service Training if school used for training, from the perspective of the principal team, the teachers and trainers, contributes to initial training of teachers coming from Higher Education Institutions (HEIs). Based on a qualitative approach we used a questionnaire for getting data. Data collection among respondents was done by intentional sampling. The study was carried out in a public elementary and secondary school in Pelotas, Rio Grande do Sul State. Some resulting questions marked out the study, such as: which types and what the characteristics are of the possible contribution of the school used for training? How is really built the relationship between the school used for training and the HEIs? The main theoretical bases were Alarcão (2001), Nóvoa (1992; 1995), and Pepper (2001; 2008). Some elements may be emphasized as a synthesis of the study: The three groups mentioned the importance of supervised pre-service training for initial training of future teachers. Training was characterized as the place of practice, as well as the moment to practice learned theories. In addition, institutions also were recognized as having very different roles, in other words, the university as the place of theory and the school as the place of practice. A criticism was presented to the distance, normally perceived, between the school used for training and the university. Another criticism regarded the fact that training happens for a too short time, something more emphasized by teachers and of the principal team. It seems advisable to see the school used for training as cotraining institution for the future teacher in activities that are only developed during training. A question to be considered is that the school has not the role of a mere "recipient" of trainers, but, even according to some laws, a more formative role. Supervised Pre-Service Training, although a mandatory component, and despite being thought as an articulator of knowledge, included in curricular syllabuses, seems to lacks mechanisms that could structure its recognition as a place in the professional field connected to curricular university activities.